Do obese patients with type A aortic dissection benefit from total arch repair through a partial upper sternotomy? - Xie, Lin-Feng; He, Jian; Wu, Qing-Song; Qiu, Zhi-Huang; Jiang, De-Bin; Gao, Hang-Qi; Chen, Liang-wan (Frontiers in Cardiovascular Medicine, 2023)
Background Minimal research has been performed regarding total arch replacement through partial upper sternotomy in patients with acute type A aortic dissection who are obese, and the safety and feasibility of this procedure need to be further investigated. The present study investigated the potential clinical advantages of using a partial upper sternotomy versus a conventional full sternotomy for total arch replacement in patients who were obese. Methods This was a retrospective study. From January 2017 to January 2020, a total of 65 acute type A aortic dissection patients who were obese underwent total arch replacement with triple-branched stent graft. Among them, 35 patients underwent traditional full sternotomy, and 30 patients underwent partial upper sternotomy. The perioperative clinical data and postoperative follow-up results of the two groups were collected, and the feasibility and clinical effect of partial upper sternotomy in total arch replacement were summarized. Results The in-hospital mortality rates of the two groups were similar. The total operative time, cardiopulmonary bypass, aortic cross-clamp, cerebral perfusion, and deep hypothermic circulatory arrest times were also similar in both groups. The thoracic drainage and postoperative red blood cell transfusion volumes in the partial upper sternotomy group were significantly lower than those in the full sternotomy group. Mechanical ventilation time was shorter in the partial upper sternotomy group than that in the full sternotomy group. Additionally, the incidences of pulmonary infection, hypoxemia, and sternal diaphoresis were lower in the partial upper sternotomy group than those in the full sternotomy group. Conclusion This study showed that total arch replacement surgery through a partial upper sternotomy in patients with acute type A aortic dissection who are obese is safe, effective, and superior to full sternotomy in terms of blood loss, postoperative blood transfusion, and respiratory complications.